2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26509
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Learning Eliminates the Negative Impact of Gender Stereotypes on Women’s Self-Concept

Abstract: Cultural stereotypes about women's "fit" and ability in technical fields are alive and well. Such cultural beliefs can make their way into women's psyches, and when this happens women's self-conceptions in computing suffer, namely, self-efficacy, sense of belonging, and identification with computing. The current research examines whether collaborative learning methods in the form of study support programs can cancel out the negative relationship between women's endorsement of negative gender stereotypes and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This may be due to the difference in how they view their self-concept and how they react to stress and aggression. Stout and Tamer (2016) suggested that women tend to have a more negative self-concept, are more prone to suffer from depressive symptoms (Moieni, Irwin, Jevtic, Olmstead, Breen, & Eisenberger, 2015), and are more likely to exhibit forms of relational aggression (e.g. gossip, rumours) (Loflin & Barry, 2016) than men which make women experience more difficulties in their adjustment process and lead them to be more vulnerable to isolation and alienation.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the difference in how they view their self-concept and how they react to stress and aggression. Stout and Tamer (2016) suggested that women tend to have a more negative self-concept, are more prone to suffer from depressive symptoms (Moieni, Irwin, Jevtic, Olmstead, Breen, & Eisenberger, 2015), and are more likely to exhibit forms of relational aggression (e.g. gossip, rumours) (Loflin & Barry, 2016) than men which make women experience more difficulties in their adjustment process and lead them to be more vulnerable to isolation and alienation.…”
Section: Resultsmentioning
confidence: 99%
“…This may be implemented via class discussion. Another advantage to class discussion is that it fosters a sense of collaboration in class, which is also known to be beneficial for women in computing [17]. Students may also feel more "connected" to their instructor, if the instructor shares personal stories about their own experiences learning computing concepts.…”
Section: Best Practicesmentioning
confidence: 99%
“…Students' sense of belonging is widely recognized as relevant to persistence and engagement in academics [22,46,49]. The importance of belonging may be additionally influential for students who are underrepresented in the field and for students about whom negative stereotypes exist [45].…”
Section: Research On Students' Belongingmentioning
confidence: 99%